2016
DOI: 10.1111/ejn.13190
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse traumatic axonal injury in mice induces complex behavioural alterations that are normalized by neutralization of interleukin-1β

Abstract: Widespread traumatic axonal injury (TAI) results in brain network dysfunction, which commonly leads to persisting cognitive and behavioural impairments following traumatic brain injury (TBI). TBI induces a complex neuroinflammatory response, frequently located at sites of axonal pathology. The role of the pro-inflammatory cytokine interleukin (IL)-1β has not been established in TAI. An IL-1β-neutralizing or a control antibody was administered intraperitoneally at 30 min following central fluid percussion injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 89 publications
(130 reference statements)
1
28
1
Order By: Relevance
“…In order to measure locomotor activity and obtain a behavioral profile of the mice, the MCSF test was used (Meyerson, Augustsson, Berg, & Roman, ) on 8‐ and 11‐month‐old mice. This test has previously been adopted to study functional outcomes and treatment effects after traumatic brain injury (Ekmark‐Lewen, Lewen, Meyerson, & Hillered, ; Ekmark‐Lewen et al., , ). In the MCSF test, animals are placed in a novel arena, divided into different zones.…”
Section: Methodsmentioning
confidence: 99%
“…In order to measure locomotor activity and obtain a behavioral profile of the mice, the MCSF test was used (Meyerson, Augustsson, Berg, & Roman, ) on 8‐ and 11‐month‐old mice. This test has previously been adopted to study functional outcomes and treatment effects after traumatic brain injury (Ekmark‐Lewen, Lewen, Meyerson, & Hillered, ; Ekmark‐Lewen et al., , ). In the MCSF test, animals are placed in a novel arena, divided into different zones.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we previously showed that systemic administration of a neutralizing IL-1β antibody attenuated the inflammatory response, cerebral edema, and tissue loss and improved cognitive outcome in a focal TBI model in mice. Furthermore, neutralization of IL-1β attenuated the complex behavioral and cognitive dysfunction observed in mice subjected to the central fluid percussion model [10]. Similarly, systemic post-injury administration of a human recombinant interleukin-1 receptor antagonist resulted in attenuated neuronal loss and oligodendrocyte death after lateral fluid-percussion brain injury [11,12].…”
Section: Introductionmentioning
confidence: 95%
“… 27 , 28 Recently, neutralization of IL-1β normalized the complex behavioral changes observed in a diffuse TBI model, the central fluid percussion model, in mice. 29 The mechanisms explaining the behavioral improvements observed by IL-1β neutralization have not been established.…”
Section: Introductionmentioning
confidence: 99%